2012
DOI: 10.1111/j.1440-1789.2012.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain‐derived neurotrophic factor (BDNF) mRNA expression and presence of BDNF‐immunoreactive granules in the spinocerebellar ataxia type 6 (SCA6) cerebellum

Abstract: Spinocerebellar ataxia type 6 (SCA6) is an autosomal-dominant neurodegenerative disorder caused by a small expansion of tri-nucleotide (CAG) repeat encoding polyglutamine (polyQ) in the gene for α(1A) voltage-dependent calcium channel (Ca(v) 2.1). Thus, this disease is one of the nine neurodegenerative disorders called polyQ diseases. The Purkinje cell predominant neuronal loss is the characteristic neuropathology of SCA6, and a 75-kDa carboxy-terminal fragment (CTF) of Ca(v) 2.1 containing polyQ, which remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Similar results were obtained when the expression of TrkB was specifically downregulated in CFs (Choo et al, 2017). Accordingly, qRT-PCR analysis of post-mortem cerebellar samples from SCA6 patients revealed a significant decrease in the expression of BDNF transcripts (Takahashi et al, 2012), and an impairment in synaptic elimination of weaker CFs in the Ca v 2.1[84Q] SCA6 mouse model (Jayabal et al, 2017).…”
Section: Alterations In Circuit Wiring In the Cerebellar Cortex Of Scassupporting
confidence: 70%
“…Similar results were obtained when the expression of TrkB was specifically downregulated in CFs (Choo et al, 2017). Accordingly, qRT-PCR analysis of post-mortem cerebellar samples from SCA6 patients revealed a significant decrease in the expression of BDNF transcripts (Takahashi et al, 2012), and an impairment in synaptic elimination of weaker CFs in the Ca v 2.1[84Q] SCA6 mouse model (Jayabal et al, 2017).…”
Section: Alterations In Circuit Wiring In the Cerebellar Cortex Of Scassupporting
confidence: 70%
“…A lack of BDNF will likely affect pre-and postsynaptic functions and may lead to morphological changes and synaptic failure. In fact, many studies have documented a decrease in BDNF levels in neurodegenerative diseases, most notably in AD (Narisawa-Saito et al, 1996;Connor et al, 1997;Nagahara et al, 2009), HD (Zuccato et al, 2008) and Spinocerebellar ataxia (Takahashi et al, 2012). Administration of BDNF has been shown to be neuroprotective against age-related hippocampal synaptic loss (Nagahara et al, 2009(Nagahara et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-localization of CREB and cytoplasmic Ca v 2.1 aggregates was confirmed in human SCA6 Purkinje cells, suggesting that the suppression of CREB-mediated transcription takes place in SCA6 Purkinje cells. Indeed, we recently found that the brain derived neurotrophic factor (BDNF) mRNA, which is regulated by the CREB-mediated transcription, is reduced in SCA6 human cerebellum [26]. It is also important to note that the CREB and p-CREB were not reduced even when the rCTF was over-expressed in the nuclei by tagging the rCTF with NLS.…”
Section: Discussionmentioning
confidence: 99%